Analysis of methods for solving the problem of 3d face detection (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
This article considers the problem of face detection in the case of 3D and discusses the current state of the problem , describes the principles of the existing systems of three-dimensional detection. Methods for solving a key problem in the field of three-dimensional face detection - obtaining three-dimensional information about a face are presented. Common methods of 3D face detection are considered.
Keywords: face detection, SFM, PCA, restoration of 3D model of the face.